Pembuatan Alat Penetas Telor Otomatis Untuk Peningkatan Penghasilan Peternak Desa Kertamukti Kec. Cibitung Kabupaten Bekasi - Sigit Panca Priyana; Josua Bertuah Turi Sitompul; Johannes Sipayung; Iyen Martupa Naibaho; Alfian Ady Saputra (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
The need for food in the form of chicken meat in Indonesia in one year is 3.43 million tons in 2021 (based on BPS). This can only be fulfilled if the continuity of supply chain availability runs smoothly from hatchery, rearing to the food industry. In the International Joint Agreement contained in the DEVISION FOR SUSTAINABLE DEVELOPMENT GOALS (DSDG) which is noted in the second point "Zero Hungry" or zero hunger that every country aims to overcome hunger in the world. Based on these conditions, researchers will design an automatic egg incubator with a capacity of 200 eggs with hatching temperature conditions between 38°C - 40°C and humidity between 60-70% RH with incubation time of 21 days. The method used in this study was to maintain optimal conditions for hatching eggs with temperatures between 38°C - 40°C with 200 eggs being incubated with humidity in the incubation room between 60-70% RH with an egg hatching period of 21 days. If this research trial is successful, then for the sake of sufficient meat in the food industry an egg incubator with a large capacity of 1000 eggs will be created. By designing an automatic heat control system using a controller program and sensors with input humidity and temperature and output in the form of heat and humidity as needed which is regulated by a microcomputer-based control system and a timer in this study is expected to meet food needs by meeting the requirements for smooth supply chains, availability of raw materials in the form of eggs and the adequacy of the required electric power. This research is expected to produce optimal conditions of temperature 38° C - 40°C and humidity 60-70%RH the air in the egg hatching room can be maintained during incubation until the eggs are hatched. By using the Arduino programming language using a control system, namely the input goes into the control system and continues to be output with the control system based on a microcomputer and a timer, the working system of heating, humidity and motor rotation can be known and measured, in the form of numbers and has units.